Book culture of the Peoples’ Republic of Tuva: positive and negative tendencies - Maadyr, Maya S. (The New Research of Tuva, 2011)
Article analyzes the processes of book culture development in the Peoples’ Republic of Tuva, distinguishes the achievements and problems.